A economia da inovação e o impacto das tecnologias ao longo das épocas - Figueira, Adalberto Guedes (Brasil, 2023)
Technological innovation is related to various aspects within economic activities, being understood as an indispensable instrument for increasing the productivity and competitiveness of organizations. The general objective of this monograph was to describe the technologies that emerged from the first industrial revolution, with the specific objectives of describing the technologies and innovations involved in each revolution, discussing the technological innovations in Industry 4.0 and addressing the challenges of this industry in the market. Brazilian. This work was justified due to the accelerated growth of technological innovations that directly impact the development of society. The methodology used was descriptive, bibliographical and quantitative in nature, analyzing historical factors correlated to economic innovation. In the results and discussions, the technological innovations that emerged in the industrial revolutions, the existing technological innovations in Industry 4.0 and the challenges of Industry 4.0 for the Brazilian market were addressed. Thus, analyzing how these elements were established within the development of society and how these innovations boosted economic growth over time.